1992
DOI: 10.1055/s-0038-1646353
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Thrombomodulin Induce Receptor-Mediated Endocytosis in Human Saphenous Vein Endothelial Cells

Abstract: SummaryThe membrane glycoprotein thrombomodulin (TM) is an essential endothelial cell (EC) cofactor, which forms a 1:1 stoichiometric complex with thrombin. Binding of thrombin to the high affinity TM receptor transforms its procoagulant activity into an anticoagulant potential, by activating protein C. The fate of TM in the presence of thrombin is still unclear: some authors claim that the thrombin-TM complex is internalized in EC, while others find this complex to be stable for at least 2 h at 37° C on the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…IgG fractions of those serum samples inhibited the activation of protein C and bound to a recombinant version of the EGF-like portion of thrombomodulin. In addition, it has been demonstrated that the levels of expression of thrombomodulin on endothelial cells are reduced by internalization of the thrombomodulin-thrombin complex in the presence of the antibody to thrombomodulin [53].…”
Section: Discussionmentioning
confidence: 99%
“…IgG fractions of those serum samples inhibited the activation of protein C and bound to a recombinant version of the EGF-like portion of thrombomodulin. In addition, it has been demonstrated that the levels of expression of thrombomodulin on endothelial cells are reduced by internalization of the thrombomodulin-thrombin complex in the presence of the antibody to thrombomodulin [53].…”
Section: Discussionmentioning
confidence: 99%
“…Quite appropriate to its name, thrombomodulin acting in concert with proteins C and S converts thrombin into an antithrombotic enzyme that inactivates coagulation factors [67]. Hence, any intervention that may compromise thrombomodulin function, including targeting drugs that may block, inhibit or shed thrombomodulin, has the potential to shift the balance towards thrombosis [68,69]. Indeed, some of such interventions induced or aggravated thrombosis in animal models [48].…”
Section: Constitutively Expressed Transmembrane Glycoproteins Enrichementioning
confidence: 99%
“…The molecular and functional characteristics of membrane thrombomodulin have been well delineated [6, 71. Cell-surface expression of thrombomodulin is regulated by a number of mechanisms including a tumour-necrosisfactor-mediated process which regulates transcription of the thrombomodulin gene [ 81, internalization by receptor-mediated endocytosis [9] and proteolytic cleavage from the endothelial cell membrane [lo]. The relative role of each of these mechanisms in the surface expression of thrombomodulin has yet to be defined.…”
mentioning
confidence: 99%